Introduction to Mathematical Logic (Edition 2017) - Podnieks, Karlis (My University, 2017)
This is Edition 2017. Read the NEW Edition 2021 at https://dspace.lu.lv/dspace/handle/7/53914. Hyper-textbook for students in mathematical logic. First order languages. Axioms of constructive and classical logic. Proving formulas in propositional and predicate logic. Glivenko's theorem and constructive embedding. Axiom independence. Interpretations, models and completeness theorems. Normal forms, skolemization and resolution method. Herbrand's theorem. Sections 1, 2, 3 represent an extended translation of the corresponding chapters of the book: V. Detlovs, Elements of Mathematical Logic, Riga, University of Latvia, 1964, 252 pp. (in Latvian).
Hyper-textbook for students in mathematical logic, Edition 2017
Keywords: logic; mathematical logic; propositional logic; predicate logic; constructive logic; intuitionistic logic; first order logic; completeness theorem; model theory; normal forms; resolution; resolution method; Herbrand theorem